Assessing students' factual, conceptual, and procedural knowledge of Newton's Laws of motion - Cashata, Zerihun Anibo; Seyoum, Desta Gebeyehu; Alemu, Shemelise Assefa (Universitas PGRI Kanjuruhan Malang, 2022)
The study aims to assess the difficulties in factual knowledge, conceptual understanding, and procedural knowledge of physics pre-service teachers on Newton’s laws of motion. The study was conducted in four colleges of teacher education located in the southern regions of Ethiopia .This study employed descriptive survey methods. For data collection, 14- Factual-Knowledge Test, 19- Conceptual understanding test and 3-open ended questionaries’ were used. Descriptive statics such as means, standard deviations, percentages, frequencies, and Minnesota Assessment of problem solving Rubric are used for written solution, where 136 students were involved in the quantitative part. They were consulted in the qualitative part of this study. The findings reveal a lack of conceptual understanding (61 percent) and procedural knowledge among pre-service physics teachers. This is evident in their low performance in the category or indicator dimensions of using, determining, and understanding problems (56 percent), in writing laws and principles (61%), and in determining the correct answer to problems (59 percent). A reasonable recommendation is given to solve the problem so that the pre-service physics teacher has adequate conceptual and procedural knowledge.